Mechanical engineering at the University of Minho - Flores, Paulo (2012)
This paper draws upon research aiming at investigating teaching and learning at higher education within the so-called Bologna Process. It discusses the ways in which students learn at Engineering Education and it analyses their implications for redesigning initial training and rethinking teachers’ role. Data were gathered through interviews and questionnaires. A questionnaire was designed including both closed and open-ended questions. Four levels of information were included: biographic data (gender, age, initial training, current job position, etc), academic education (reasons for choosing Mechanical Engineering, reasons for selecting University of Minho, expectations about Mechanical Engineering course, etc), transition from University to labor market (difficulties faced, scope and nature of the work, etc) and graduate and post-graduate interests (areas, type and organization for high level courses, specific courses, Masters’ and PhD courses). Background characteristics, such as years of experience, academic years of experience at the current job were also included. Overall, findings suggest a positive evaluation of initial training, namely the ways students adapted to university, relationship between students, and length of their practicum. They also highlight a number of issues to be improved: a more hands-on approach, a better pedagogical intervention from lecturers, a more adequate articulation between content knowledge at secondary school and university education.